A Systematic Review of the Strength, Durability, and Microstructure Properties of Concrete Incorporating Glass Powder - Oualid Semmana; Mohammed Ali M. Rihan; Zakaria M. Barrie; Chukwuemeka Daniel; Tareg Abdalla Abdalla (Engineering Reports)
ABSTRACT Concrete is one of the most widely used construction materials worldwide; its primary component, cement, contributes substantially to natural resource depletion and greenhouse gas emissions. Alternative materials are being explored to mitigate these impacts and reduce concrete's environmental footprint. This review focuses on the potential of waste glass powder (GP) as a partial substitute for cement in concrete, examining its influence on mechanical properties, durability, and microstructural performance. Drawing from a wide range of studies published in reputable peer‐reviewed journals (e.g., Wiley, ACI, MDPI, Elsevier), the analysis reveals that an optimal GP substitution level of 10%–20%, offers significant improvements in concrete durability, particularly in resistance to chloride permeability, sulfuric acid attack, and performance under high temperatures. GP contributes through its micro‐filling ability, which reduces porosity and pozzolanic reaction, forming a secondary calcium silicate hydrate (C‐S‐H) gel that enhances binding strength. However, substituting GP above 25%–30% may reduce compressive strength due to decreased flowability and increased porosity. Overall, GP demonstrates considerable potential as an eco‐friendly, cost‐effective additive that improves concrete resilience and supports sustainable construction practices. This review not only consolidates existing research but also highlights GP's dual effects on concrete's microstructure and pozzolanic reactions, suggesting further optimization of GP content and synergies with other materials to enhance resilience across diverse applications. Therefore, future research should optimize GP content and investigate synergies with other materials for broader concrete applications.